Geografski informacijski sistemi v Sloveniji 2009-2010 - Perko, Drago; Zorn, Matija (GIS v Sloveniji, 2010)
This is the tenth volume ('Geographic information systems in Slovenia, 2009-2010') in a row, featuring thirty-four research and survey papers on the current use of geographic information systems (GIS) in Slovenia. GIS offer an excellent opportunity for interdisciplinary cooperation. This allows knowledge from a specific discipline to be expanded with findings from related disciplines, which enables further development of individual disciplines and synergy effects in finding solutions to emerging problems.